1993
DOI: 10.1111/j.1600-0536.1993.tb03533.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration threshold of non‐occluded nickel exposure in nickel‐sensitive individuals and controls with and without surfactant

Abstract: Most cases of primary nickel sensitization are caused by occluded exposure to nickel released from earrings, buttons, etc. Nickel-sensitive females are both domestically and occupationally exposed to trace amounts of nickel. The present study was designed to define the minimum eliciting threshold concentration of nickel exposure in previously nickel-sensitized individuals, after open application on normal forearm skin with and without surfactant. A dilution series of NiCl2, ranging from 0.1 to 4000 ppm nickel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…Experimentally it has also been shown that the highest rate of nickel penetration from different salt solution occurs primarily in the fi rst 24 h [54] and the low and variable penetration of nickel across isolated skin supports the view of the importance of transfollicular diffusion, although the intercellular avenue should not be neglected [58] . Patchy skin reactions after testing of nickel allergy are also compatible with high concentrations of nickel in the appendages, especially in the concentration range between defi nite positive and negative reactions [44,59,60] .…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally it has also been shown that the highest rate of nickel penetration from different salt solution occurs primarily in the fi rst 24 h [54] and the low and variable penetration of nickel across isolated skin supports the view of the importance of transfollicular diffusion, although the intercellular avenue should not be neglected [58] . Patchy skin reactions after testing of nickel allergy are also compatible with high concentrations of nickel in the appendages, especially in the concentration range between defi nite positive and negative reactions [44,59,60] .…”
Section: Discussionmentioning
confidence: 99%
“…Patch testing with 5% nickel sulfate (2.0 mg/cm 2 ) in petrolatum is used in the European baseline series, whereas 2.5% (1.0 mg/cm 2 ) is used in North America (Figure ) . Nickel sulfate is less irritant than nickel chloride, although nickel chloride more accurately resembles real‐life exposure to nickel alloys in contact with human sweat . In general, doubtful and irritant patch test reactions to nickel are less common than those to other metals, such as cobalt and chromium .…”
Section: Diagnosing Nickel Allergymentioning
confidence: 99%
“…The ability of nickel ions to cause a dermal reaction in sensitized individuals depends on their concentration, the exposed skin area and the exposure duration (Flint, 1998). Generally, a concentration exceeding 1.5 lg Ni chloride per cm 2 of skin in an open application is required to elicit dermatitis in sensitized individuals (Menné and Calvin, 1993). However, lower concentrations may also induce an allergic reaction if other irritants or allergens are present in parallel (Pedersen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%